2011
DOI: 10.1177/097226291101500303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bond Rating on Share Prices

Abstract: Credit-rating agencies play a key role in financial markets by helping to reduce the informative asymmetry between lenders and borrowers regarding the creditworthiness of the latter. While the various bond-rating areas have been extensively evaluated for mature markets, similar evidence for emerging markets, such as India, is limited. In particular, the issues relating to know the efficiency of stock markets to assimilate bond-rating changes announcements made by rating agencies from time to time have been ign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The literature on credit rating changes in emerging market has assessed the impact of sovereign credit ratings and capital markets (Christopher et al, 2012; Mutize & Gossel, 2018; Reisen & Von Maltzan, 1998). There are few studies on credit rating changes in Indian market (Lal & Mitra, 2011; Sehgal & Mathur, 2013), and their results are contradictory. Thus, with growing importance of Indian capital market and changing regulatory frameworks, it is important to analyze the stock market reaction to credit rating changes for Indian listed entities and further develop the extant literature for developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature on credit rating changes in emerging market has assessed the impact of sovereign credit ratings and capital markets (Christopher et al, 2012; Mutize & Gossel, 2018; Reisen & Von Maltzan, 1998). There are few studies on credit rating changes in Indian market (Lal & Mitra, 2011; Sehgal & Mathur, 2013), and their results are contradictory. Thus, with growing importance of Indian capital market and changing regulatory frameworks, it is important to analyze the stock market reaction to credit rating changes for Indian listed entities and further develop the extant literature for developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over time, the enlargement of bond and stock markets, the spread of CRA activity outside the USA, the growing need for issuers to be rated, and the subsequent improvement in the availability of financial data have allowed other fields of investigation to emerge. In particular, studies focusing on other geographical areas have been implemented, first involving European countries such as the United Kingdom (Barron et al ., ), France (François‐Heude and Paget‐Blanc, ), Spain (Abad‐Romero and Robles‐Fernandez, , ) and Portugal (Pacheco, ); then, the Asia‐Pacific area: Japan (Behr and Güttler, ), Australia (Choy et al ., ; Creighton et al ., ) and New Zealand (Elayan et al ., ) and more recently, emerging markets (Parisi and Perez, ; Poon and Chan, ; Lal and Mitra, ). Most often, the features of these stock markets differ from their US counterparts in terms of size, liquidity and depth.…”
Section: Theoretical Background and Empirical Evidencementioning
confidence: 99%
“…A related issue is whether the investors react more strongly where the change in bond rating is from investment to speculative grade in case of downgrades. Holthausen and Leftwich (1986); Hite and Warga (1997) ;Creighton, Gower and Richards (2007); Benjamin (2008) and Lal and Mitra (2011) found that downgrades resulting in change in category of bond from investment to speculative grade extract a larger price response than any other downgrades. Similarly, it is expected that where the bond ratings are in the speculative grade the shareholders may respond more intensely due to higher risk of default of such bonds (Goh and Ederington, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies do cover the rating changes, but their impact on security prices is not examined (Bajaj, 1998;Sehgal & Arora, 2004). Only a few studies explore this relationship in the Indian context (Mohindroo, 2008;Lal and Mitra, 2011). Moreover, other important areas such as the effect of firm characteristics on the relationship between bond rating changes and stock return behaviour have not been studied.…”
Section: Introductionmentioning
confidence: 99%